Implikasi Putusan Mahkamah Konstitusi Terhadap Sistem Peradilan Indonesia - Arini Asriyani; Asti Dwiyanti (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
The decisions of the Constitutional Court (MK) have a significant impact on the Indonesian justice system. The Constitutional Court is an institution tasked with overseeing and ensuring legal compliance with the state constitution. MK decisions are often an important reference in the formation of legal policies and changes in the justice system. some important implications of the Constitutional Court's decision on the Indonesian justice system. First, the Constitutional Court's decision can be a law or regulation not in accordance with the constitution, the decision becomes the basis for revising or abolishing unconstitutional laws. This can lead to changes in judicial practice and overall legal policy. Second, the Constitutional Court's decision can strengthen the protection of human rights. The Constitutional Court has the authority to examine the constitutionality of laws relating to human rights. If the Constitutional Court decides that a law violates human rights, the decision will encourage the enforcement of those rights and increase the protection of human rights in Indonesia. Furthermore, the Constitutional Court's decision can provide a new direction in the interpretation of the constitution. The Constitutional Court is often faced with complex and controversial issues involving the interpretation of the constitution. The Constitutional Court's decision in this case can provide new guidelines and interpretations of the constitution, which have the potential to change the understanding and application of law in Indonesia. Finally, the Constitutional Court's decision can strengthen the independence of the judiciary. The Constitutional Court has an important role in maintaining the balance of power between the executive, legislative and judicial institutions. The Constitutional Court's decision affirming the independence of the judiciary can strengthen the authority and role of the judiciary in carrying out its duties in a fair and neutral manner. The Constitutional Court's decision has significant implications for the Indonesian justice system. MK decisions can influence the interpretation and application of law, strengthen the protection of human rights, provide new directions in the interpretation of the constitution, and strengthen the independence of the judiciary. It is important for all legal and judicial stakeholders to pay attention to the Constitutional Court's decision and understand its impact on the Indonesian justice system.